1° GAM Video Festival : Video collections from Europe. - Bongiovanni, Pierre; Castro Flórez, Fernando; Gehrig, Claudia; Iten, André; Jongbloed, Marjorie; Muir, Gregor; Rutten, Bart; Van Assche, Christine; Volpato, Elena; Willemsen, Paul (Torino : GAM (Galleria Civica d'Arte Moderna e Contemporanea), 2002)
Laurette, Matthieu ; Grimonprez, Johan ; Paik, Nam June ; Marker, Chris ; Filliou, Robert ; Long, Richard ; Roehr, Peter ; Dibbets, Jan ; Corsino, N+N ; Melitopulos, Angela ; Kogut, Sandra ; Suermondt, Robert ; D'Haeseleer, Kurt ; Verdin, Walter ; Gilbert & George ; Sanchez Blanco, Domingo ; Okón, Yoshua ; Sanchez Castillo, Fernando ; Marty, Enrique ; Signer, Roman ; Viola, Bill ; Closuit, Geneviève ; Rist, Pipilotti ; Odenbach, Marcel ; Antille, Emmanuelle ; d'Armagnac, Ben ; Vasulka, Steina ; General Idea ; Arnold, Robert ; Weibel, Peter ; Günther, Ingo ; Waliczky, Tamas
Engels & Frans & Italiaans & Nederlands
GAM Video Festival 2002 : Video collections from Europe, GAM (Galleria Civica d'Arte Moderna e Contemporanea), Torino, 8 - 14 settembre 2002
boek